2022
DOI: 10.1111/cas.15684
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 trial of zolbetuximab in Japanese patients with CLDN18.2+ gastric or gastroesophageal junction adenocarcinoma

Abstract: Zolbetuximab is a chimeric monoclonal antibody that targets claudin‐18.2, a candidate biomarker in patients with advanced gastric/gastroesophageal cancer. This nonrandomized phase 1 study (NCT03528629) enrolled previously treated Japanese patients with claudin‐18.2–positive locally advanced/metastatic gastric/gastroesophageal cancer in two parts: Safety (Arms A and B, n = 3 each) and Expansion (n = 12). Patients received intravenous zolbetuximab 800 mg/m2 on cycle 1, day 1 followed by 600 mg/m2 every 3 weeks (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
(92 reference statements)
1
4
0
Order By: Relevance
“…In the phase I trials, zolbetuximab was well tolerated across the entire dose range (33-1,000 mg/m 2 ), and treatment-related AEs mostly were of grades 1-3. 15,35,36 A similar safety profile was observed in the phase II MONO and FAST trials. 27,31 In the MONO study, the most common AEs were nausea, vomiting and fatigue, and 20% of patients (n=11) discontinued treatment due to treatment-emergent AEs (TEAEs).…”
Section: Safety Profile and Adverse Events Common Adverse Events Asso...supporting
confidence: 59%
See 2 more Smart Citations
“…In the phase I trials, zolbetuximab was well tolerated across the entire dose range (33-1,000 mg/m 2 ), and treatment-related AEs mostly were of grades 1-3. 15,35,36 A similar safety profile was observed in the phase II MONO and FAST trials. 27,31 In the MONO study, the most common AEs were nausea, vomiting and fatigue, and 20% of patients (n=11) discontinued treatment due to treatment-emergent AEs (TEAEs).…”
Section: Safety Profile and Adverse Events Common Adverse Events Asso...supporting
confidence: 59%
“…gov identifier: NCT00909025). 35 Patients received 800 mg/ m 2 intravenous zolbetuximab on cycle 1, day 1, followed by 600 mg/m 2 or 1,000 mg/m 2 every 3 weeks. Similarly to the previous phase I study, this trial did not identify any dose-limiting toxicities.…”
Section: Clinical Trials and Efficacy Phase I Trials: Safety And Dosi...mentioning
confidence: 99%
See 1 more Smart Citation
“…A phase I study in Japan evaluating zolbetuximab monotherapy in previously treated Japanese patients with CLDN 18.2-positive locally advanced G/GEJ adenocarcinoma showed that 11 of 17 patients achieved stable disease ( 30 ). MONO, a phase II study, showed that zolbetuximab monotherapy in recurrent/refractory CLDN 18.2-positive gastric cancer had an ORR of 9% and a clinical benefit rate of 23% ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of patient reported outcomes, maintenance therapy with zolbetuximab lowered symptom burden and increased quality of life compared to EOX alone (95). Given that GC is very prevalent amongst Asian populations (96), a phase I trial (NCT03528629) of zolbetuximab in CLDN18.2-positive locally advanced/metastatic GC/ GEJ patients from Japan was conducted, which yielded no new safety concerns (88). ILUSTRO Trial (NCT03505320): A phase II clinical trial was conducted to assess safety and efficacy of zolbetuximab alone (cohort 1, n=30), zolbetuximab in combination with mFOLFOX6 (cohort 2, n=21) or zolbetuximab plus pembrolizumab (cohort 3, n=3) in advanced GC/GEJ adenocarcinoma with moderate (≥50% but <75%) to high (≥75%) CLDN18.2+ staining.…”
Section: Cldn182 (Zolbetuximab)mentioning
confidence: 99%